2019
DOI: 10.3390/genes10050353
|View full text |Cite
|
Sign up to set email alerts
|

A Premature Stop Codon in RAF1 Is the Priority Candidate Causative Mutation of the Inherited Chicken Wingless-2 Developmental Syndrome

Abstract: The chicken wingless-2 (wg-2) mutation is inherited in an autosomal recessive fashion, and the resulting phenotype in mutant (wg-2/wg-2) individuals is a developmental syndrome characterized by absent wings, truncated legs, craniofacial as well as skin and feather defects, and kidney malformations. Mapping and genotyping established that the mutation resides within 227 kilobases (kb) of chromosome 12 in a wg-2 congenic inbred line. A capture array was designed to target and sequence the candidate region along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Wojnowski et al ( 1998 ) noted thinner and less differentiated dermal and epidermal layers in Raf1 −/− mice, while Yamaguchi et al ( 2004 ) found that heart‐specific Raf1 −/− mice exhibited cardiac dysfunction and apoptosis. More recently, the recessive‐acting wingless2 mutation found in Gallus gallus —which results in a phenotype strikingly similar to this syndrome with truncated limbs, craniofacial, cardiac, and skin/feather defects—was linked to a homozygous premature stop codon in Raf1 (Youngworth & Delany, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wojnowski et al ( 1998 ) noted thinner and less differentiated dermal and epidermal layers in Raf1 −/− mice, while Yamaguchi et al ( 2004 ) found that heart‐specific Raf1 −/− mice exhibited cardiac dysfunction and apoptosis. More recently, the recessive‐acting wingless2 mutation found in Gallus gallus —which results in a phenotype strikingly similar to this syndrome with truncated limbs, craniofacial, cardiac, and skin/feather defects—was linked to a homozygous premature stop codon in Raf1 (Youngworth & Delany, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 More recently, the recessive-acting wingless2 mutation found in Gallus galluswhich results in a phenotype strikingly similar to this syndrome with truncated limbs, craniofacial, cardiac and skin/feather defectswas linked to a homozygous premature stop codon in Raf1. 37 These observations lead us to conjecture that the Mendelian disease and by inference ACFS may be caused by impaired RAF1 signaling. Hence, it will be worthwhile checking for mutations in RAF1, its upstream regulators and downstream effectors in previously reported ACFS cases.…”
Section: Discussionmentioning
confidence: 99%
“…10 More recently, the recessive-acting wingless2 mutation found in Gallus gallus – which results in a phenotype strikingly similar to this syndrome with truncated limbs, craniofacial, cardiac and skin/feather defects – was linked to a homozygous premature stop codon in Raf1 . 37…”
Section: Discussionmentioning
confidence: 99%